Corporal and a poet… Biographic conditioning of professional paths of female directors (Biograficzne badania nad twórczością. Teoria i empiria, 2016)
The article is of propaedeutical character in the field of research into biographies and socio-cultural conditioning of performing artistic professions by women. The author refers primarily to data available from interviews with female directors and to the already available (auto) biographical materials. The problem of research into the profession of female directors is a part of much broader deliberations concerning the artist, the creative process, the work of art and the context and circumstances in which it was created. The text presents the results of research into professional paths of female directors and the author presents the elements of their career, particularly the key events, strategies and motives that provided their professional career path with more dynamics, but also the difficulties they come across in their artistic work.